Association between hibernating myocardium and collateral circulation in patients with coronary chronic total occlusion - Liu, Yaqi; Chen, Yongjun; Zhang, Feifei; Liu, Bao; Wang, Jianfeng; Xu, Mei; Wang, Yuetao; Shao, Xiaoliang (Frontiers in Cardiovascular Medicine, 2024)
Objective: To explore the association between the quantity of hibernating myocardium (HM) and collateral circulation in patients with coronary chronic total occlusion (CTO).Materials and Methods: 88 CTO patients were retrospectively analyzed who underwent evaluation for HM using both 99m Tc-sestamibi Single photon emission computed tomography ( 99m Tc-MIBI SPECT) myocardial perfusion imaging (MPI) combined with 18 F-fluorodeoxyglucose positron emission tomography ( 18 F-FDG PET) myocardial metabolism imaging (MMI). They were divided into two groups according Rentrop grading: the poorly/well-developed collateral circulation group (PD/WD group, Rentrop grades 0-1/2-3). After adjusting for the potential confounding factors and conducting a stratified analysis, we explored the association between the HM index within CTO region and the grading of collateral circulation.In the WD group, the HM index was notably higher than PD group (46.2±15.7% vs. 20.9±16.7%, P<0.001). When dividing the HM index into tertiles and after adjusting for potential confounders, we observed that the proportion of patients with WD rose as the HM index increased (OR: 1.322, 95% CI: 0.893-1.750, P<0.001), the proportion of patients with WD was 17.4%, 63.3%, and 88.6% for Tertile 1 to Tertile 3.This increasing trend was statistically significant (OR: 1.369, 95% CI: 0.873-1.864, P<0.001), especially between Tertile 3 versus Tertile 1 (OR: 4.330, 95% CI: 1.459-12.850, P=0.008). Curve fitting displaying an almost linear positive correlation between the two.The HM index within CTO region is an independent correlation factor for the grading of coronary collateral circulation. A greater HM index corresponded to an increased likelihood of WD.